Suppression of Poxvirus Replication by Resveratrol - Cao, Shuai; Realegeno, Susan; Pant, Anil; Satheshkumar, Panayampalli S.; Yang, Zhilong (Frontiers in Microbiology, 2017)
Poxviruses continue to cause serious diseases even after eradication of the historically deadly infectious human disease, smallpox. Poxviruses are currently being developed as vaccine vectors and cancer therapeutic agents. Resveratrol is a natural polyphenol stilbenoid found in plants that has been shown to inhibit or enhance replication of a number of viruses, but the effect of resveratrol on poxvirus replication is unknown. In the present study, we found that resveratrol dramatically suppressed the replication of vaccinia virus, the prototypic member of poxviruses, in various cell types. Resveratrol also significantly reduced the replication of monkeypox virus, a zoonotic virus that is endemic in Western and Central Africa and causes human mortality. The inhibitory effect of resveratrol on poxviruses is independent of vaccinia virus N1 protein, a potential resveratrol binding target. Further experiments demonstrated that resveratrol had little effect on vaccinia virus early gene expression, while it suppressed vaccinia virus DNA synthesis, and subsequently post-replicative gene expression.